The Impact of Flexible Working Arrangements on IT Employee Productivity: The Mediating Role of Job Quality - Gatot Sasongko; Marcelin Herly Joy Luhukay (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2026)
The implementation of flexible working arrangements (FWA) has become increasingly prevalent in the information technology (IT) sector, particularly following the growing demand for work flexibility in digital work environments. However, empirical findings regarding the effect of FWA on employee productivity remain inconsistent, indicating the need for further investigation by incorporating mediating factors. This study aims to analyze the effect of flexible working arrangements on IT employee productivity, with job quality serving as a mediating variable. This study employs a quantitative approach using a survey method. Primary data were collected through an online questionnaire distributed to IT employees in Indonesia who have experience working under flexible working systems. The sampling technique combined convenience sampling and purposive sampling, with the number of respondents meeting the analytical requirements for PLS-SEM. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4. The results indicate that flexible working arrangements have a positive and significant effect on both job quality and IT employee productivity. Furthermore, job quality is also found to have a positive and significant effect on employee productivity. The indirect effect analysis reveals that job quality partially mediates the relationship between flexible working arrangements and employee productivity. These findings provide theoretical implications by reinforcing the job demands–resources perspective in the context of flexible work, as well as practical implications for organizations, particularly in the IT sector, in designing flexible work policies that not only enhance flexibility but also improve job quality and employee productivity.